A metáfora na leitura em língua estrangeira : efeitos de uma intervenção pedagógica - Farias, Claudia Valeria Vieira Nunes (2006)
This study is focused on the comprehension of metaphors in foreign language texts. The specific aims of the research are: a) to verify to what extent the presence of metaphors represents an obstacle to the comprehension of a foreign language text and b) to investigate how this obstacle could be overcome or minimized through pedagogic intervention focused on metaphor. The study is based on two theoretical axes: theory of reading and theories of metaphor. In the first case, an interactional and socio-historical view of reading (Nunes, 1992, Amorim, 1997) was adopted; in the second case, a cognitive approach to metaphor, within which this trope is viewed as a figure of thought and not merely as a figure of language (Lakoff e Johnson, 1980/2002), was followed. The methodology adopted is qualitative and the action research was carried out with secondary school FL pupils. The instruments consisted of two written activities, group verbal protocol and pedagogic intervention. A text rich in metaphorical language was used as reading material. The analysis of the data indicated that there was enhancement in the metaphor comprehension in the students reading process after the pedagogic intervention, which corroborates the claim advocated by several scholars (Lazar, 2003, Lima, 2005) that teaching about metaphors brings benefits to language learning in general and to reading.